2000
DOI: 10.1126/science.289.5476.107
|View full text |Cite
|
Sign up to set email alerts
|

Interconnected Feedback Loops in the Neurospora Circadian System

Abstract: In Neurospora crassa, white collar 1 (WC-1), a transcriptional activator and positive clock element, is rhythmically expressed from a nonrhythmic steady-state pool of wc-1 transcript, consistent with posttranscriptional regulation of rhythmicity. Mutations in frq influence both the level and periodicity of WC-1 expression, and driven FRQ expression not only depresses its own endogenous levels, but positively regulates WC-1 synthesis with a lag of about 8 hours, a delay similar to that seen in the wild-type clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
350
2
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(380 citation statements)
references
References 28 publications
25
350
2
3
Order By: Relevance
“…109) showing similarity to a calcium/calmodulin-dependent protein kinase (CAMK-1) also occurred among the sequences down-regulated in the DFvMAT1-2-1 mutant as there is a multiple interaction between the WCC complex and CAMK-1. WCC activates the transcription of frq, a gene encoding the circadian clock protein, FREQUENCY (FRQ), and FRQ -meanwhile repressing frq transcription -exerts a positive feedback on levels of the WC proteins (Lee et al 2000). Posttranslational mechanisms also regulate the circadian clock functions through phosphorylation of these proteins maintaining thus the proper operation of the clock.…”
Section: Discussionmentioning
confidence: 99%
“…109) showing similarity to a calcium/calmodulin-dependent protein kinase (CAMK-1) also occurred among the sequences down-regulated in the DFvMAT1-2-1 mutant as there is a multiple interaction between the WCC complex and CAMK-1. WCC activates the transcription of frq, a gene encoding the circadian clock protein, FREQUENCY (FRQ), and FRQ -meanwhile repressing frq transcription -exerts a positive feedback on levels of the WC proteins (Lee et al 2000). Posttranslational mechanisms also regulate the circadian clock functions through phosphorylation of these proteins maintaining thus the proper operation of the clock.…”
Section: Discussionmentioning
confidence: 99%
“…It involves interlocked feedback loops (Glossop et al 1999;Lee et al 2000;Ripperger & Schibler 2001). Moreover, experiments showed that multiple phosphorylations of the PER protein have differential effects on the protein degradation and translocation in the nucleus (Vanselow et al 2006;Xu et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These negative factors, which physically interact with each other, producing heterodimers (e.g. mouse PER-CRY, or fly PER-TIM), are later shuttled back to the nucleus where they repress the positive circadian transcription factors, thereby downregulating their own transcription (Darlington et al 1998;Kume et al 1999;Lee et al 2000;Alabadi et al 2001). The decrease in abundance in the negative factors later in the circadian cycle gradually leads to their own derepression, allowing the positive transcription factor to drive a new circadian cycle.…”
Section: Circadian Clocks: Posttranscriptional and Translational Regumentioning
confidence: 99%